Evaluation of Mathoulin Surgical Approach in the Treatment of Scaphoid Waist Nonunion with Definite Proximal Avascular Necrosis (Journal of Pharmaceutical Negative Results, 2022)
Introduction: Avascular necrosis (AVN) is a rather common complication of scaphoid fractures, particularly scaphoid waist nonunion, which may occur even after surgical fixation. In the present investigation we aimed to evaluate the efficacy of Mathoulin technique in the surgical fixation of scaphoid waist nonunion with definite proximal AVN.Material and Methods: A total of 35 cases of scaphoid waist non-union with definite proximal AVN undergoing surgical fixation in a major tertiary referral orthopaedic hospital in northwestern Iran in 2021 were enrolled. Postoperative pain intensity, grip strength (based on modified mayo wrist score) and carpal range of motion (angles of movements) were evaluated at four time intervals, 1, 4.5, 6 and 9 months following Mathoulin surgical fixation.Results: A total of 35 patients, 28 (80%) male and 7 (20%) female, with a mean age of 28.96 ± 1.89 were investigated. By the end of the 9th month, no patients complained of severe pain, and 33 (94.28%) participants only reported mild pain. Carpal flexion, extension, supination and pronation angles significantly improved following surgery. Grip strength in 29 patients improved significantly. Wrist function Union as achieved in 33 (97.29%) patients.Conclusion: Mathoulin method in patients with proximal definite AVN with Scafoid Waist fusion leads to a reduction in pain intensity, improvement of motor angles, grip strength and satisfaction with surgery to a desirable extent